Estrogen‐related receptor alpha is an AMPK‐regulated factor that promotes ischemic muscle revascularization and recovery in diet‐induced obese mice. Issue 9 (22nd June 2022) - Sopariwala, Danesh H.; Rios, Andrea S.; Park, Mi Kyung; Song, Min Sup; Kumar, Ashok; Narkar, Vihang A.
Abstract: Obesity and type II diabetes are leading causes of peripheral arterial disease (PAD), which is characterized by vascular insufficiency and ischemic damage in the limb skeletal muscle. Glycemic control is not sufficient to prevent progression of PAD, and molecular targets that can promote muscle neo‐angiogenesis in obesity and diabetes remain poorly defined. Here, we have investigated whether nuclear receptor estrogen‐related receptor alpha (ERRα) can promote ischemic revascularization in the skeletal muscles of diet‐induced obese (DIO) mice. Using muscle‐specific ERRα transgenic mice, we found that ERRα overexpression promotes revascularization, marked by increased capillary staining and muscle perfusion in DIO mice after hindlimb ischemic injury. Furthermore, ERRα facilitates repair and restoration of skeletal muscle myofiber size after limb ischemia in DIO mice. The ameliorative effects of ERRα overexpression did not involve the prevention of weight gain, hyperglycemia or glucose/insulin intolerance, suggesting a direct role for ERRα in promoting angiogenesis. Interestingly, levels of endogenous ERRα protein are suppressed in the skeletal muscles of DIO mice compared to lean controls, coinciding with the suppression of angiogenic gene expression, and reduced AMPK signaling in the DIO skeletal muscles. Upon further investigating the link between AMPK and ERRα, we found that AMPK activation increases the expression and recruitment of ERRα protein to specific angiogenic gene promoters in muscle cells. Further, the induction of angiogenic factors by AMPK activators in muscle cells is blocked by repressing ERRα. In summary, our results identify an AMPK/ERRα‐dependent angiogenic gene program in the skeletal muscle, which is repressed by DIO, and demonstrate that forced ERRα activation can promote ischemic revascularization and muscle recovery in obesity.